Risk Assessment for Metalworking Fluids and Respiratory Outcomes - Robert M. Park (Elsevier, 2019)
Background: Metalworking fluids (MWFs) are mixtures with inhalation exposures as mists, dusts, and vapors, and dermal exposure in the dispersed and bulk liquid phase. A quantitative risk assessment was performed for exposure to MWF and respiratory disease. Methods: Risks associated with MWF were derived from published studies and NIOSH Health Hazard Evaluations, and lifetime risks were calculated. The outcomes analyzed included adult onset asthma, hypersensitivity pneumonitis, pulmonary function impairment, and reported symptoms. Incidence rates were compiled or estimated, and annual proportional loss of respiratory capacity was derived from cross-sectional assessments. Results: A strong healthy worker survivor effect was present. New-onset asthma and hypersensitivity pneumonitis, at 0.1 mg/m3 MWF under continuous outbreak conditions, had a lifetime risk of 45%; if the associated microbiological conditions occur with only 5% prevalence, then the lifetime risk would be about 3%. At 0.1 mg/m3, the estimate of excess lifetime risk of attributable pulmonary impairment was 0.25%, which may have been underestimated by a factor of 5 or more by a strong healthy worker survivor effect. The symptom prevalence associated with respiratory impairment at 0.1 mg/m3 MWF was estimated to be 5% (published studies) and 21% (Health Hazard Evaluations). Conclusion: Significant risks of impairment and chronic disease occurred at 0.1 mg/m3 for MWFs in use mostly before 2000. Evolving MWFs contain new ingredients with uncharacterized long-term hazards. Keywords: Benchmark dose, Hypersensitivity pneumonitis, Metalworking fluids, Occupational asthma, Survivor effect